Estimating the number of children exposed to parental psychiatric disorders through a national health survey - Padoin Cintia V; Bassani Diego G; Philipp Diane; Veldhuizen Scott (BMC, 2009)
Abstract Objective Children whose parents have psychiatric disorders experience an increased risk of developing psychiatric disorders, and have higher rates of developmental problems and mortality. Assessing the size of this population is important for planning of preventive strategies which target these children. Methods National survey data (CCHS 1.2) was used to estimate the number of children exposed to parental psychiatric disorders. Disorders were diagnosed using the World Psychiatric Health Composite International Diagnostic Interview (WMH-CIDI) (12 month prevalence). Data on the number of children below 12 years of age in the home, and the relationship of the respondents with the children, was used to estimate exposure. Parent-child relations were identified, as was single parenthood. Using a design-based analysis, the number of children exposed to parental psychiatric disorders was calculated. Results Almost 570,000 children under 12 live in households where the survey respondent met criteria for one or more mood, anxiety or substance use disorders in the previous 12 months, corresponding to 12.1% of Canadian children under the age of 12. Almost 3/4 of these children have parents that report receiving no mental health care in the 12 months preceding the survey. For 17% of all Canadian children under age 12, the individual experiencing a psychiatric disorder is the only parent in the household. Conclusion The high number of children exposed causes major concern and has important implications. Although these children will not necessarily experience adversities, they possess an elevated risk of accidents, mortality, and of developing psychiatric disorders. We expect these estimates will promote further research and stimulate discussion at both health policy and planning tables.